2014
DOI: 10.11607/prd.1472
|View full text |Cite
|
Sign up to set email alerts
|

Share Page: Share on facebook Share on twitter Share on email Share on google_plusone_share More Sharing Services Back Volume 34 , Issue 1 January/February 2014 Pages e1–e8 Interdisciplinary Approach for Treating a Large Through-and-Through Periapical Defect Using Guided Tissue Regeneration: A Case Report

Abstract: A number of diagnostic and management challenges exist for achieving complete regeneration of large through-and-through periapical lesions. An unfavorable endodontic outcome may occur as a result of uncontrolled infection or unpredictable bone healing. This article presents a case with a 15 × 15-mm through-and-through periapical lesion and persistent gingival swelling. Endodontic microsurgery and guided tissue regeneration were performed using a resorbable membrane and osseous substitute. A 2-year postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There have been many clinical studies published where GTR therapy was used in cases of periradicular and coronoapical bone defect that have shown promising results. [456] However, these cases did not have associated soft-tissue fenestrations. Established literature does not show any long-term clinical study with a large sample size of mucosal fenestration as the finding is rare.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…There have been many clinical studies published where GTR therapy was used in cases of periradicular and coronoapical bone defect that have shown promising results. [456] However, these cases did not have associated soft-tissue fenestrations. Established literature does not show any long-term clinical study with a large sample size of mucosal fenestration as the finding is rare.…”
Section: Discussionmentioning
confidence: 94%
“…Use of resorbable collagen membrane used as GTR therapy has also proved to be highly successful when treating endodonticperiodontal lesions and has shown good results, relating to bone growth and connective tissue attachment. [457]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported the successful resolution of periapical defects with a combined application of GTR and bone grafts[ 16 17 18 19 20 ] or with GTR alone. [ 21 22 23 ] Some have resorted to combined technique of GTR and Platelet rich plasma.…”
Section: Discussionmentioning
confidence: 99%